Exploration and classification of intensive care nurses' clinical decisions: a greek perspective - Karra, Vassiliki; Papathanassoglou, Elizabeth; Lemonidou, Chryssoula; Sourtzi, Panayota A.; Giannakopoulou, Margarita (My University, 2014)
Aim: The recording, identification, coding and classification of clinical decisions by intensive care nurses. Background: Clinical decision-making is an essential dimension of nursing practice as through this process nurses make choices to meet the goals of patient care. Intensive care nurses' decision-making has received attention because of the complexity and urgency associated with it, however, the types of nurses' clinical decisions have not been described systematically. Methods: Qualitative content analysis of daily diaries of clinical decisions recorded during nursing work by 23 purposefully selected intensive care nurses from three major hospitals of Greece. The process of data collection and analysis continued until the point of theoretical saturation. Findings: Eight categories of nursing clinical decisions emerged including decisions related to: (1) evaluation, (2) diagnosis, (3) prevention, (4) intervention, (5) communication with patients, (6) clinical information seeking, (7) setting of clinical priorities and (8) communication with health care professionals. Psychological assessment and support decisions were scarce, whereas patient input in care decisions appeared to be limited. The most frequent types of decisions were regarding intervention (29%), evaluation (25%) and clinical setting of priorities (17%), while clinical information seeking (3%) and communication with patients decisions (2%) were the least frequent. Additionally, recorded decisions were ranked in order of degree of urgency and of dependency on medical order. Non-urgent decisions were 78% of the total and 60% of nurses' intervention decisions were independent of medical order and were related to basic nursing care. Conclusions: Intensive care nurses make multiple decisions that seem to be in line with the nursing process, although the latter is not officially implemented in Greek ICUs. Relevance to clinical practice: The types and frequency of clinical decisions made by intensive care nurses are related to features of ICU work environment, their professional autonomy and accountability, as well as their perceptions of their clinical role.
Keywords: Clinical decisions; Content analysis; Intensive care; Nurses; Qualitative study; Types